Supplier Selection Of Upper Arm And Lower Arm Pantograph Jack Using AHP And TOPSIS Methods - Hery Hamdi Azwir; Fuad Hasan; Hirawati Oemar (Jurnal Rekayasa Sistem Industri, 2020)
Cost reduction and multi sourcing program is one of the ways used by companies to survive in business competition. Supplier selection process conducted by PT. MTM aims to get suppliers capable of supplying the needs in a sustainable manner with quality products and competitive prices. The company needs a method to select suppliers that can supply upper arm and lower arm components for pantograph jack products. The research is done through analyzing supplier selection process by PT. MTM, examines the criteria used, and then implements the AHP and TOPSIS methods in the process to gain alternative supplier priorities and reduced purchase costs. To speed up data processing, this study utilizes Expert Choice 11 software. The result of analysis using AHP and TOPSIS is two suppliers will supply the components in PT. MTM. Keywords: AHP, multi sourcing, cost reduction, panthograph jack, supplier, TOPSIS